Urban Growth Determinants for the State of Kelantan Opinions of the State's Policy Makers - Wan Ismail, Wan Ibrisam Fikry (Fakulti Ukur dan Harta Tanah, 1996)
The paper presents views of key officers with regard to the factors that accelerate urban growth in Kelantan. These factors can be divided into four main categories namely: locational factor, economic factor, infrastructure factor and political and administrative factor. The survey using questionnaires was conducted in 1992. Results gained from this research indicate that Kelantan needs to improve its infrastructure and facililies as well as encourages more public and private investors to locate in Kelantan in order to help the towns grow.